Influence of Alloying Additives on The Adhesive Properties of Steels: Atomic Level Simulation - AlMotasem, Ahmed Tamer (JOURNAL OF ADVANCES IN PHYSICS, 2018)
In the present work we report atomistic molecular dynamics simulation results on adhesion force between self-mated iron/iron, iron/vanadium, iron-cementite and iron/titanium surfaces has been determined and we found that iron/cementite surface exhibits lower adhesive force than that of iron/iron surface. The results showed that adhesion, quantified by the work of adhesion, decreased as the vanadium content increased and highest reduction was obtained for 10 at.% vanadium and 7.5 at.% for titanium. Furthermore, the variation of adhesion force with temperature was studied in the temperature range between 300-700 K and we found that the adhesive force generally is lowered at higher temperature.